Spiritualitas Anak Usia Dini dalam Perspektif Yesus: Analisis Eksegetis Markus 10:13–16 - Yudhy Sanjaya; Agiana Her Visnhu Ditakristi; Upa Silaen (Real Kiddos: Jurnal Pendidikan Anak Usia Dini, 2026)
The development of pedagogy in early childhood Christian Religious Education (CRE) often emphasizes the cognitive transmission of doctrine, while the spiritual dimension of children as theological subjects has not been sufficiently articulated through exegetical readings focused on Gospel texts. This article analyzes Mark 10:13–16 to explain how the passage presents children as those who are received by Jesus and presented as a model for receiving the Kingdom of God, and to examine its relevance for the pedagogy of early childhood Christian Religious Education. This study employs a descriptive qualitative method with a narrative and lexical exegetical approach to Mark 10:13–16, enriched by a reading of the parallel texts in Matthew 19:13–15 and Luke 18:15–17 as well as a review of literature on child theology and Christian education. The specific contribution of this article lies in the formulation of three characteristics of early childhood spirituality derived from the reading of this passage, namely receptivity to grace, incarnational relationality, and the paradigmatic function of the child for the life of discipleship. The findings show that Mark 10:13–16 not only affirms Jesus’ acceptance of children, but also positions them as theological subjects who reveal the logic of the Kingdom of God. These findings imply the need to develop a more child-friendly, relational, and community-based pedagogy of Christian Religious Education that involves family and church, while giving space to children’s experiences of faith within the Christian community. Keywords: Mark 10:13–16; children's spirituality; Christian religious education; narrative exegesis; pedagogy of children’s faith formation Abstrak Perkembangan pedagogi Pendidikan Agama Kristen (PAK) anak usia dini kerap berfokus pada transmisi kognitif doktrin, sementara dimensi spiritualitas anak sebagai subjek teologis belum banyak dirumuskan melalui pembacaan eksegetis yang terfokus pada teks Injil. Artikel ini menganalisis Markus 10:13–16 untuk menjelaskan bagaimana perikop tersebut menampilkan anak sebagai pihak yang diterima Yesus dan dijadikan acuan dalam menerima Kerajaan Allah, serta menelaah relevansinya bagi pedagogi PAK anak usia dini. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan eksegesis naratif dan leksikal terhadap Markus 10:13–16, yang diperkaya dengan pembacaan teks paralel Matius 19:13–15 dan Lukas 18:15–17 serta studi pustaka teologi anak dan pendidikan Kristen. Kontribusi khusus artikel ini terletak pada perumusan tiga ciri spiritualitas anak usia dini dari pembacaan perikop tersebut, yakni reseptivitas terhadap anugerah, relasionalitas yang inkarnasional, dan fungsi paradigmatik anak bagi kehidupan murid. Hasil penelitian menunjukkan bahwa Markus 10:13–16 tidak hanya menegaskan penerimaan Yesus terhadap anak-anak, tetapi juga menempatkan mereka sebagai subjek pembinaan iman yang mengungkapkan logika Kerajaan Allah. Temuan ini berimplikasi pada pengembangan pedagogi PAK yang lebih ramah anak, berbasis relasi, melibatkan keluarga dan gereja, serta memberi ruang bagi pengalaman iman anak dalam komunitas Kristen. Kata Kunci: Markus 10:13-16; spiritualitas anak; pendidikan agama Kristen; eksegesis naratif; pedagogi iman anak